Monitoring ocular disease via optical nanostructures potentially applicable to corneal contact lens products - Bader AlQattan; Mohamed Elsherif; Fahad Alam; Haider Butt (NPG Asia Materials, 2024)
Abstract Ocular diseases can cause vision problems or even blindness if they are not detected early. Some ocular diseases generate irregular physical changes in the eye; therefore, reliable diagnostic technology for continuous monitoring of the eye is an unmet clinical need. In this study, a pulsed laser (Nd:YAG) was used to create optical nanostructures on a hydrogel-based commercial contact lens. Simulations were used to determine the spacing of the nanostructures, which were then produced and tested on the lens in ambient humidity and fully hydrated environments. The nanostructures produced a 4° diffraction angle difference in response to the environmental changes. Vision obstruction was considered while designing the nanostructure features on the lens. The curved nanostructures exhibited a series of visible rainbow colors with an average range of 8° under normal room light. A spherical surface was also used to simulate the human eye, and application of a force (curvature change) caused the nanostructure spacing to change, influencing the visible color of the contact lenses. A smartphone camera application was used to measure the progress of ocular diseases by analyzing the RGB color values of the visible color. The nanostructures were also responsive to K+ ion variations in artificial tear fluids, with a 12 mmol L−1 sensitivity, which may allow the detection of ocular ionic strength changes.